2020
DOI: 10.1016/j.jpeds.2020.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Global Coronavirus Disease-2019 Pandemic on Early Childhood Development: Short- and Long-Term Risks and Mitigating Program and Policy Actions

Abstract: the Sesame Workshop, the MacArthur Foundation, and the Lego Foundation. The sponsors of work by the authors on this manuscript had no role in (1) study design; (2) the collection, analysis, and interpretation of data; (3) the writing of the report; or (4) the decision to submit the paper for publication. The authors declare no conflicts of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
211
0
23

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(263 citation statements)
references
References 45 publications
1
211
0
23
Order By: Relevance
“…Research has documented the benefits of support from families, educators, and friends for well‐being across domains, yet the support that children and adolescents can draw from these sources is likely compromised because the important others in their lives must also navigate all the stressors and uncertainties accompanying the pandemic. These include disruptions to parents’ work and economic circumstances (e.g., Ananat & Gassman‐Pines, 2020), reductions in young children’s access to child care (Yoshikawa et al, 2020), and teachers and schools managing the abrupt transition for school‐age youth to online learning (Rothstein, 2020).…”
Section: Life Course Perspective: Development Transitions and Trajementioning
confidence: 99%
See 1 more Smart Citation
“…Research has documented the benefits of support from families, educators, and friends for well‐being across domains, yet the support that children and adolescents can draw from these sources is likely compromised because the important others in their lives must also navigate all the stressors and uncertainties accompanying the pandemic. These include disruptions to parents’ work and economic circumstances (e.g., Ananat & Gassman‐Pines, 2020), reductions in young children’s access to child care (Yoshikawa et al, 2020), and teachers and schools managing the abrupt transition for school‐age youth to online learning (Rothstein, 2020).…”
Section: Life Course Perspective: Development Transitions and Trajementioning
confidence: 99%
“…Such experiences tax parents’ emotional well‐being, limiting the psychological resources needed to attend to children’s socioemotional and cognitive needs and increasing the use of harsher and less responsive parenting strategies (Conger & Elder, 1994; Kalil, 2013). Social and economic upheaval also boosts the risk of family violence, and prolonged economic challenges and confinement during the current pandemic could lead to increases in intimate partner violence and child abuse (Yoshikawa et al, 2020). Similarly, research has documented the links between how parents and children fare when facing global health crises: In a retrospective study, rates of parents’ PTSD were significantly higher for those who experienced SARS and H1N1 pandemic‐related isolation or quarantine, and most parents diagnosed with PTSD had children who were similarly diagnosed (Sprang & Silman, 2013).…”
Section: Life Course Perspective: Development Transitions and Trajementioning
confidence: 99%
“…Anecdotal evidence in Kenya shows that the COVID-19 pandemic is contributing to deteriorating optimal environments that threaten children’s early development and has direct health impacts on caregivers and children [ 11 , 12 , 13 ]. Strategies are required to prioritize a range of ECD interventions during the COVID-19 pandemic to support caregivers so that they can meet the needs of their young children.…”
Section: Kenyan Contextmentioning
confidence: 99%
“…15 Issue 5 DOI 10.5195/jyd.2020.996 America's Moment 19 survey revealed that 30% of young people report they have been more unhappy or depressed, and nearly the same number report worrying about having their basic needs met The stress of the pandemic is overwhelming for many families. Parents are unable to be a buffer of stress for their children due to their own financial concerns, worry, and social isolation as they struggle to provide and care for their children's basic needs (Yoshikawa et al, 2020).…”
Section: Youth Mental Healthmentioning
confidence: 99%